Consenso brasileiro de ronco e apneia do sono: aspectos de interesse aos ortodontistas - Chaves Junior, Cauby Maia (2011)
The objective of this article is to clarify the positions of the medical societies that have worked together to establish a consensus regarding the clinical and laboratory parameters involved in sleep-disordered breathing, particularly snoring and obstructive sleep apnea syndrome (OSAS). Orthodontists have gradually come to take part in multidisciplinary teams that act in the area of human sleep, but few know about the uniformity coordinated by the Brazilian Association of Sleep. Clinical and scientific studies from the field of dentistry (particularly orthodontics) also must observe and follow these diagnosis and treatment criteria established by the Brazilian medical community.